Phenotypic spectrum and extent of DNA methylation defects associated with multilocus imprinting disturbances. (June 2016) - Bens, Susanne; Kolarova, Julia; Beygo, Jasmin; Buiting, Karin; Caliebe, Almuth; Eggermann, Thomas; Gillessen-Kaesbach, Gabriele; Prawitt, Dirk; Thiele-Schmitz, Susanne; Begemann, Matthias; Enklaar, Thorsten; Gutwein, Jana; et al.
Aim: To characterize the genotypic and phenotypic extent of multilocus imprinting disturbances (MLID).Materials & methods: We analyzed 37 patients with imprinting disorders (explorative cohort) for DNA methylation changes using the Infinium HumanMethylation450 BeadChip. For validation, three independent cohorts with imprinting disorders or cardinal features thereof were analyzed (84 patients with imprinting disorders, 52 with growth disorder, 81 with developmental delay).Results: In the explorative cohort 21 individuals showed array-based MLID with each one displaying an Angelman or Temple syndrome phenotype, respectively. Epimutations in ZDBF2 and FAM50B were associated with severe MLID regarding number of affected regions. By targeted analysis we identified methylation changes of ZDBF2 and FAM50B also in the three validation cohorts.Conclusion: We corroborate epimutations in ZDBF2 and FAM50B as frequent changes in MLID whereas these rarely occur in other patients with cardinal features of imprinting disorders. Moreover, we show cell lineage specific differences in the genomic extent of FAM50B epimutation.